Influence of Bias Potential Magnitude on Structural Engineering of ZrN-Based Vacuum-Arc Coatings - Sobol’, O.V.; Postelnyk, H.O.; Pinchuk, N.V.; Meylekhov, A.A.; Zhadko, M.A.; Andreev, A.A.; Stolbovoy, V.A. (Physics and Chemistry of Solid State, 2021)
The creation of the scientific foundations for the structural engineering of ultrathin nanolayers in multilayer nanocomposites is the basis of modern technologies for the formation of materials with unique functional properties. It is shown that an increase in the negative bias potential (from -70 to -220 V) during the formation of vacuum-arc nanocomposites based on ZrN makes it possible not only to control the preferred orientation of crystallites and substructural characteristics but also changes the conditions for conjugation of crystal lattices in ultrafine (about 8 nm) nanolayers.